THE RIGHTS OF PRIVATE ECONOMIC ACTORS UNDER THE WORLD TRADE ORGANIZATION AGREEMENTS IN INDONESIA - Soeparna, Intan (UI Scholars Hub, 2012)
Nothing in the Uruguay Round mentions directly about rights of private economic actors. It seems that the relationship to private economic actors (or may be individual) does not exist within the WTO Agreements, because as a general rule, private parties are not legal subjects of the international legal order. However, this article will prevail upon this situation, by looking closer at the essence of the WTO Agreements to discern the rights of private economic actors that derive from the WTO. The main question of this article is to what extent then Indonesia is dealing with the rights of private economic actors under the WTO Agreements? The background of this questionis because four years after ratifying the WTO Agreements, Indonesia has been facing what is arguably the most serious multidimensional crisis in 1997, some difficult situations have arisen from the crisis; therefore, the society hesitated to accept the open world trading system. The society seemed look askance to the implementation of the WTO Agreements. But Indonesian Government took major step to reduce the skepticism of society toward liberalization, by readjusting its national laws conform to the WTO Agreements with the intention to support the rights of national economic actors under the WTO Agreements in order to achieve total benefits of the WTO rules.